2003
DOI: 10.1021/jf025711q
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Enantiomeric Composition for the Assessment of the Authenticity of Fruit Beverages

Abstract: Enantiomeric compositions of chiral terpenes in commercial fruit beverages were examined by solid phase microextraction-gas chromatography (SPME-GC). Optimization of the method was accomplished on the basis of some parameters involved in the extraction, such as heating temperature and extraction time, that provided the highest peak areas, 60 degrees C and 2 min being the optimal values. With the proposed method relative standard deviation (RSD) values from three replicates ranging from 2 to 12% were obtained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…With regard to the enantiomeric composition of S-b-pinene, it varied in a narrower range (between 80 and 93%) in all samples. As the occurrence of both enantiomers of b-pinene and, on the contrary, the enantiomeric purity of limonene in natural samples have been described by other authors [20] and in our own laboratory [21], it can be concluded that the predominance of S-limonene in the M. piperita essential oil analysed in this work may be attributed to the addition of synthetic aromas to enhance the sample natural aroma. From these results, we could state that Lavandin and peach essential oils appeared not to have been handled and, therefore, they may be defined as natural samples.…”
Section: Resultssupporting
confidence: 71%
“…With regard to the enantiomeric composition of S-b-pinene, it varied in a narrower range (between 80 and 93%) in all samples. As the occurrence of both enantiomers of b-pinene and, on the contrary, the enantiomeric purity of limonene in natural samples have been described by other authors [20] and in our own laboratory [21], it can be concluded that the predominance of S-limonene in the M. piperita essential oil analysed in this work may be attributed to the addition of synthetic aromas to enhance the sample natural aroma. From these results, we could state that Lavandin and peach essential oils appeared not to have been handled and, therefore, they may be defined as natural samples.…”
Section: Resultssupporting
confidence: 71%
“…Neither δ-terpinene nor α-terpinene was a major component in any EO studied, and their presence did not seem to influence the activity of the EO that contained them. The LC 50 s of (4 S )(-)-limonene and (4 R )(+)-limonene were 5 and 6.2 mg/dm 3 , respectively; however, the Citrus EO used in this study contained only (4 R )(+)-limonene [ 21 , 22 ] ( Table 1 ). Therefore, we compared the LC 50 of Citrus EOs with the LC 50 of (4 R )(+)-limonene and found that (4 R )(+)-limonene, the fourth most active T, had the same insecticidal activity as Citrus EOs.…”
Section: Resultsmentioning
confidence: 87%
“…As far as the stereochemical analysis is concerned, it has also been occasionally reported that SPME offers the possibility of isolating selectively the chiral constituents from complex matrices under non-racemization conditions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%